Malaysian Oil Palm Workers Are in Pain: Hazards Identification and Ergonomics Related Problems - Nur Syazwani, Mohd Nawi; Baba, M. Deros; Mohd Nizam A., Rahman; Ezrin Hani, Sukadarin; Norani, Nordin (2016)
Agricultural activities have always been associated with hazards and injuries. Most common injuries experienced by workers are health, safety and ergonomic injuries. It stems from many causes, such as the use of manual tools, incorrect working position, inadequate rest and overloading. This paper aims to reveal the daily hazardous work task of oil palm plantation workers with highlighting the ergonomics problems and risk of injury they faced. Observations of work tasks and distribution of Modified Nordic Questionnaire (MNQ) were performed for every work unit. Worker’s activities and posture while performing work tasks were recorded extensively using camera and video recordings for ergonomics analysis. Results from the observation and questionnaire survey conducted, showed that oil palm plantation workers are exposed to the risk of dangerous work every day. Fresh fruit bunches cutter and loose fruit collectors were having highest body pain complaints and almost from them are having low back pain problems. Therefore, it is necessary for an immediate action from the management in order to determine the current prevalence of ergonomic injuries. Using of manual tools should be avoided and plantation workers should be provided with ergonomics machines that can help them reduce their workload and injuries.